Code Mixing in Instagram Captions among Indonesian Youth: A Sociolinguistic Study - Miza Rahmatika Aini (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigates the semantic features employed in food and beverage advertisements published on Instagram. The study aims to understand how lexical choices, connotative strategies, and meaning relations are employed to construct brand image, elicit emotional resonance, and influence consumer preferences. Data were collected from ten official advertising posts of popular food and beverage brands that commonly appear on Indonesian users' feeds between January and June 2025. A descriptive qualitative analysis was conducted using frameworks for lexical, connotative, and relational semantics. The findings reveal a consistent pattern in which advertisements combine denotative meanings to communicate product attributes, connotative meanings to evoke emotional associations, and relational meanings to establish cultural ties and social identity. In addition, the analysis shows that code mixing is frequently used as a linguistic strategy, with insertion type emerging as the dominant form, particularly through the integration of English lexical items into Indonesian sentence structures (e.g., vibes, fresh, bestie). This pattern reflects the influence of globalized digital culture and the tendency of brands to target younger, bilingual audiences. Beyond describing advertising language, this study contributes to linguistic research by demonstrating how semantic structures function in multimodal digital discourse and how meaning-making processes operate within contemporary social media communication. In addition, the findings offer practical insights for marketing studies by illustrating how strategic word choices and semantic framing can enhance brand positioning, audience engagement, and persuasive effectiveness in digital advertising environments. These insights highlight that semantic strategies are not merely stylistic elements but play a significant role in shaping consumer perception and interaction in the digital marketplace.